The resolving graph of amalgamation of cycles - Iswadi H.; Baskoro E.T.; Salman A.N.M.; Simanjuntak R. (Utilitas Mathematica, 2010)
For an ordered set W = {w1, w2,⋯, w k} of vertices and a vertex v in a connected graph G, the representation of v with respect to W is the ordered k-tuple r(v|W) = (d(v,w1),d(v,w2),⋯ ,d(v,wk)) where d(x, y) represents the distance between the vertices x and y. The set W is called a resolving set for G if every vertex of G has a distinct representation. A resolving set containing a minimum number of vertices is called a basis for G. The dimension of G, denoted by dim(G), is the number of vertices in a basis of G. A resolving set W of G is connected if the subgraph (W) induced by W is a nontrivial connected subgraph of G. The connected resolving number is the minimum cardinality of a connected resolving set in a graph G, denoted by cr(G). A cr-set of G is a connected resolving set with cardinality cr(G). A connected graph H is a resolving graph if there is a graph G with a cr-set W such that (W) = H. Let Gi be a finite collection of graphs and each G i has a fixed vertex voi called a terminal. The amalgamation Amal{Gi, voi} is formed by taking of all the Gi's and identifying their terminals. In this paper, we determine the connected resolving number and characterize the resolving graphs of amalgamation of cycles.